Yersinia infection tools—characterization of structure and function of adhesins - Mikula, Kornelia M.; Kolodziejczyk, Robert; Goldman, Adrian (Frontiers in Cellular and Infection Microbiology, 2013)
Among the seventeen species of the Gram-negative genus Yersinia, three have been shown to be virulent and pathogenic to humans and animals - Y. enterocolitica, Y. pseudotuberculosis, and Y. pestis. In order to be so, they are armoured with various factors that help them adhere to tissues and organelles, cross the cellular barrier and escape the immune system during host invasion. The group of proteins that mediate pathogen-host interactions constitute adhesins. Invasin, Ail, YadA, YadB, YadC, Pla and pH 6 antigen belong to the most prominent and best-known Yersinia adhesins. They act at different times and stages of infection complementing each other by their ability to bind a variety of host molecules such as collagen, fibronectin, laminin, β1 integrins, and complement regulators. All the proteins are anchored in the bacterial outer membrane, often forming rod-like or fimbrial-like structures that protrude to the extracellular milieu. Structural studies have shown that the anchor region forms a β-barrel composed of 8, 10 or 12 antiparallel β strands. Depending on the protein, the extracellular part can be composed of several domains belonging to the immunoglobulin fold superfamily, or form a coiled-coil structure with globular head domain at the end, or just constitute several loops connecting individual β stands in the β-barrel. Those extracellular regions define the activity of each adhesin. This review focuses on the structure and function of these important molecules, and their role in pathogenesis.